A bibliometric analysis of research trends in psychological interventions for stroke survivors: focusing on resilience and psychological well-being (2000-2024) - Li, Yaoyao; Soh, Kim Lam; Jing, Xiujuan; Wei, Lili; Saidi, Hasni Idayu; Soh, Kim Geok (Dove Medical Press, 2025)
Purpose: This study aims to conduct a bibliometric analysis of research literature on psychological interventions for stroke survivors published from 2000 to 2024, focusing on psychological resilience and psychological well-being, utilizing VOSviewer and CiteSpace. Patients and Methods: Literature data was sourced from the Web of Science Core Collection database (WoSCC). A total of 373 relevant articles published between January 1, 2000, and September 30, 2024, were included. CiteSpace and VOSviewer analyzed the literature from perspectives including authorship, country of origin, institutions, journals, references, and keywords. Results: Annual publication output has steadily increased, reaching a peak in 2023 (55 articles). Vranceanu Ana-Maria emerged as the most productive author with eight publications. The United States led in research output (98 articles) and centrality (0.32), with Harvard University being the leading institution (24 articles). “Disability and Rehabilitation” was the most productive journal (12 articles), while “Stroke” was the most co-cited journal (241 times). Recent research trends emphasized meta-analysis (strength=3.6), assessment tool validation (strength=3.49), and acceptance-based interventions (strength=2.89), mainly focusing on psychological resilience cultivation and well-being promotion. Conclusion: This bibliometric analysis reveals the increasing scholarly interest in psychological interventions for stroke survivors, particularly in resilience and psychological well-being research. The field has evolved from focusing on disease-related factors to systematic intervention research, with a growing emphasis on methodological standardization and individualized interventions. These findings provide significant theoretical and practical implications for improving psychological health services for stroke survivors. Future research should strengthen high-quality empirical studies, refine assessment tools, and innovate intervention strategies to better address the complex psychological needs of stroke survivors and enhance their resilience and psychological well-being, ultimately improving rehabilitation outcomes and quality of life for stroke survivors.